Establishing and Evaluating the Effectiveness of AAT for Residents in Nursing Home - Fifi Alviana; Yueh-Juen Hwu; Jiun-Iung Lei (Jurnal Ilmu Keperawatan Jiwa, 2021)
AAT is one of the complementary therapies in nursing homes. However, nurses lack related evidence – based AAT. The purpose of this project was to translate the best available evidence in order to improve residents’ well-being. There were four stages in this project. The first stage conducted a systematic review to identify the best available evidences on AAT. The second stage was discussed step by step according to the protocol for audit. The third stage was to educate multidisciplinary personnel to implement the protocol AAT. Lastly, we implemented the AAT protocol and compared the pre- and post- physiological, psychological and social score of residents to evaluate the effectiveness of AAT protocol. Eight residents completed the pretest and the first, second, and third posttest audits. Result from paired-t tests found significant improvements in residents’ physiological, psychological and social score. The project supports that AAT may effectively improve well-being for residents in nursing home.